Examining the variability of rock glacier meltwater in space and time in high-elevation environments of Utah, United States - Munroe, Jeffrey S.; Handwerger, Alexander L. (Frontiers in Earth Science, 2023)
Rock glaciers are common geomorphic features in alpine landscapes and comprise a potentially significant but poorly quantified water resource. To better understand rock glacier meltwater, we analyzed stable isotopes and hydrochemistry in water samples collected from late June through mid-October, 2022 at two sites in Utah, USA. In the Uinta Mountains, water was collected at springs discharging from two rock glaciers previously shown to release water in late summer sourced from internal ice. In the La Sal Mountains, water was collected at a rock glacier spring, along the main stream in a watershed containing multiple rock glaciers, and from a stream in a watershed where rock glaciers are absent. Results were considered in light of three complementary questions: 1) How consistent is the composition of rock glacier meltwater from year to year? 2) How dependent is the composition of rock glacier meltwater on lithology? and 3) How does the presence of rock glaciers in a catchment change stream water chemistry? Results confirm that water discharging from rock glaciers in the Uinta Mountains exhibits a shift from a snowmelt source to an internal ice source over the course of the melt season that is consistent from year to year. The chemistry of rock glacier water in the two study areas is notably different in ways that can be linked back to their contrasting bedrock types. And in the La Sal Mountains, the properties of water along the main stream in a rock-glacierized basin resemble the properties of water discharging from rock glaciers, and strongly contrast with the water in a catchment lacking rock glaciers. Collectively these results underscore the role of rock glaciers as an agent influencing the hydrochemistry of water in high-elevation stream systems.